Correction: Age trends in asymptomatic and symptomatic Leishmania donovani infection in the Indian subcontinent: A review and analysis of data from diagnostic and epidemiological studies. - PLOS Neglected Tropical Diseases Staff (Public Library of Science (PLoS), 2019)
[This corrects the article DOI: 10.1371/journal.pntd.0006803.].